Avoidance strategies among form four students in rural areas in an English medium science classroom - Daud, Derwina; Abdullah, Muhammad Rozman; A Wahab, Syazali Affendi (Penyelidikan, Pembangunan & Pengkomersilan, 2007)
The objectives of this study are to investigate the four types of avoidance strategies employed by Form Four students in an English-medium Science classroom and the reasons why students adopt these strategies to conceal their low proficiency. This study utilizes a quantitative approach, with an instrument adapted from the Patterns of Adaptive Learning Scales (Midgley, 2000). The instrument consists of 37 items concerning the learning environment, students' motivation, affect, and behavior. A four-point Likert scale was employed to determine respondents' views on avoidance strategies, which are grouped into four categories: Self-Handicapping, Avoidance of Help-Seeking, Avoidance of New Challenges, and Cheating. The findings reveal that most respondents turn to these avoidance strategies to cope with their low ability in the Science classroom, primarily due to the need to maintain their self-worth. Furthermore, the analysis indicates that there are other underlying reasons why students display certain avoidance strategies as a means of dealing with their inability in the Science classroom.